Factors Influence on Malaysian Generation Z’ Purchase Intention: Price Consciousness as a Moderating Variable - Sautova, Zhazira; Amlus, Mohammad Harith Bin; Suanda, Julinawati (Journal of Posthumanism, 2025)
The purpose of this paper is to examine the direct effect of perceived quality, value consciousness, environmental concern, subjective norm and perceived behavioural control, and moderating impact of price consciousness, and mediating influence of attitude on a purchase intention in the Malaysian retail industry. A quantitative research methodology will be used, and the data will be collected from 384 Malaysian customers from the age category between 18-26 years old. The findings of this study will contribute to an understanding of the importance of the chosen factors affecting on Generation Z’ purchase intention in the Malaysian retail industry.